MARKETING RESEARCH VS PARTNER SEARCH - Eshmamatova Madina (International Journal on Orange Technologies, 2021)
When a company begins to work out a new market for itself – no matter by what criteria-product, geographical, and so on, it is necessary to answer one simple question – whether it will be necessary to conduct marketing research or you can immediately look for contractors who will distribute the product in this market. The answer to this classic marketing question may require some effort from the company's management –many combinations of various factors that affect the decision on the optimal scheme of work to enter a new market are difficult to assess. Especially if there are accompanying incentive measures that distort the flow of a businessman's thoughts as a" black hole " light.